2003
DOI: 10.1002/ijc.11195
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin consumption, Helicobacter pylori positivity and gastric cancer in Mexico

Abstract: Gastric cancer (GC) incidence has not declined in Mexico.We assessed whether the intake of capsaicin (CAP), the pungent compound of chili peppers, increases the risk of GC independently of H. pylori positivity (Hp). From 1994 to 1996, a hospital-based case-control study was performed in 3 areas of Mexico; 234 cases of GC and 468 matched controls were enrolled and their diet and other characteristics were inquired. Chili pepper intake was queried by interview and CAP content of chilies was determined in a separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 19 publications
2
106
1
1
Order By: Relevance
“…Among many cancers, accumulating evidence focused on the causative effects of capsaicin-containing diets on stomach or gallbladder cancers (7,37). Stomach cancer is a major cancer expressing high levels of EGFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among many cancers, accumulating evidence focused on the causative effects of capsaicin-containing diets on stomach or gallbladder cancers (7,37). Stomach cancer is a major cancer expressing high levels of EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Capsaicin from chili peppers promoted stomach and liver cancer in BALB/c mice (5) and also induced duodenal adenocarcinoma in mice (6). Epidemiologic studies suggested a positive association between the incidence of stomach cancer and the consumption of chili pepper-rich diets (7). Capsaicin enhanced the metastasis of murine breast cancer cells by reducing the expression of apoptosis-related genes (8) and induced LNCaP prostate cancer cell proliferation by increasing androgen receptor expression through the activation of ERKs and Akt (9).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that consumption of nitrosamines in processed meats and vegetables, as well as a high salt diet both increase the risk for H. pylori induced disease. [61][62][63][64] Due to variations in diet around the world, the role of diet in the incidence of gastric carcinoma also varies. In East Asia, where the incidence of gastric carcinoma is high, diets are often high in salt content and nitrosamines (reviewed in ref.…”
Section: Cagamentioning
confidence: 99%
“…It was reported that chilli pepper consumption was associated with a 5.5-fold increase in risk of gastric cancer, whereas heavy consumption showed a 17-fold greater risk. In a subsequent study by Lopez-Carrillo et al (2003), 281 cases with gastric cancer and 523 hospital controls were interviewed with respect to the consumption of chilli peppers. Chilli pepper consumption was used as a surrogate for capsaicin intake, which was calculated based on reported levels of capsaicin in various chilli types.…”
Section: 4mentioning
confidence: 99%